Allah Melihat Ciptaaan-Nya Sungguh Amat Baik: Penanaman Pohon Bersama Masyarakat Di Desa Dolok Parmonangan Kecamatan Panribuan Kabupaten Simalungun - Simanjuntak, Pahala Jannen; Simanjuntak, Leonardo Pebriadi; Sianturi, Angelika; Pakpahan, Maria; Damanik, Stiven (Institut Agama Kristen Negeri Kupang, 2025)
The widespread destruction of God's creation is a crucial issue that must be addressed by all parties. This is because the destruction of God's creation often results from human activities. If environmental damage becomes severe, it can lead to poverty and prolonged suffering. Therefore, efforts to repair this damage must be undertaken through various methods. One way to reverse this damage is by planting trees, as has been done by the government, churches, and communities in various regions of Indonesia. Collaboration among all parties and the community will restore the beauty of God's creation. Tree planting in Dolok Parmonangan, Panribuan District, Simalungun Regency, carried out jointly by STT HKBP and the community, is a community service (PkM) initiative to preserve nature. This will ensure the land remains productive and protected from all disturbances. If left vacant, it will become a wilderness without clearings. Then, it could be claimed by others as their own property. This land, however, is customary land that can be passed down to future generations. Furthermore, through tree planting in Parmonangan Village, landslide-prone areas along Lake Toba can be gradually mitigated as the trees grow. The hope and goal of this tree-planting initiative are to raise public awareness of the need to care for the earth by planting tree species that can benefit humans and honor God as the Owner and Creator of the earth (Genesis 1:1). For God saw all of His creation, and indeed, it was very good (Genesis 1:31). Furthermore, God entrusted all of His creation to humans to care for and maintain to the best of their ability. Keywords: God's creation, tree planting, collaboration